Peningkatan Motivasi Dan Hasil Belajar Ips Melalui Strategi Index Card Match Pada Siswa Kelas VSD Muhammadiyah 7 Joyosuran Tahun Ajaran 2015/2016 - MUSTOFA, ATOK (2016)
ABSTRACT Atok Mustofa/ A510120062. Increased Motivation and Learning Outcomes IPS Through Strategy Index Card Match On SD Muhammadiyah Student Class V 7 Joyosuran Academic Year 2015/2016. The Faculty of Education, University of Muhammadiyah Surakarta.Januari, 2016. Class Action Research aims to improve motivation and learning outcomes IPS in class V students of SD Muhammadiyah 7 Joyosuran the academic year 2015/2016 through a strategy of Index Card Match. This research is a class act. The subjects of this study is the fifth grade students and teachers SD Muhammadiyah 7 Joyosuran the academic year 2015/2016. Methods of data collection using the student's motivation observation and documentation, while collecting social studies students use the test tetulis. Data were analyzed using data reduction, data display, and conclusion drawing / verification. The results showed that the implementation of the strategy index card match can increase motivation and learning outcomes IPS fifth grade students of SD Muhammadiyah 7 Joyosuran, with the following results: a) motivation of students in the first cycle were 24 students (74%) got a high score, and the the second cycle students who got high scores increase by 28 students (90%), and b) the results of social studies students at the pre-action value of the average student learning outcomes IPS 55 and as many as 12 students (38%) achieved a value ≥71, in cycle I average grade social studies students' results increased to 75 and as many as 22 students (71%) reached a value of ≥71, and the second cycle learning outcomes IPS students increased to 83 and 26 students (83%) reached a value of ≥71. Keywords: index card match, IPS learning motivation, learning outcomes IPS